Assessing Equality In Hospital Bed Distribution In North Sumatra Of June 2022 - Datitha Alodia Br Kaban, Karina; Novalinda Ginting, Chrismis; Chiuman, Linda (CV. Inara, 2023)
At the end of 2019, an outbreak of a respiratory infection occurred in the city of Wuhan, Hubei province, People's Republic of China. The disease was later named Coronavirus disease19/COVID-19, becoming a global pandemic. The unpreparedness of the government and health facilities in dealing with the presence of this pandemic exposed problems in the health care system in various parts of the world, namely equality of access to health. Problems in the health care system also affect Indonesia. Apart from the COVID-10 pandemic, in Indonesia research on the equivalence of the distribution of hospital beds and the health care system as a whole has never been conducted or at least has not been published. This research oversight does not only occur in Indonesia, not a single ASEAN member country has ever published research on the equality of the distribution of hospital beds. This research is a descriptive study that aims to assess the equivalence of the distribution of hospital beds in the province of North Sumatra. Almost all regencies/cities in North Sumatra have hospitals, except for Gunungsitoli City, with the majority of hospitals being in Medan City.